GENERASI Z DENGAN BRANDING RIDWAN KAMIL DI MEDIA SOSIAL - Nathania, Daniella; Claretta, Dyva (Jurnal Ilmiah Wahana Pendidikan, 2023)
Ahead of the 2024 general election, generation z is starting to enter the legal age to participate in voting. The form of campaigning that is synonymous with something rigid and serious is one of the factors of generation Z's ignorance of politics. A new campaign breakthrough is needed as an approach for generation z as first-time voters, namely an approach that is lighter and easier to accept by generation z. One of them is the use of social media as a campaign container. Ridwan Kamil, is one of the politicians who uses his social media as a forum for campaigning. This study aims to analyze the acceptance of generation z about political branding in Ridwan Kamil's content on Instagram @ridwankamil social media. The research method used in the research is qualitative descriptive with data collection techniques, namely interviews. The result of this study was found a difference in the acceptance of the meaning of content by informants about Ridwan Kamil's Instagram social media. From the research that has been done, there are two informants who are in the dominant hegemonic category, three people are in the negotiated reading category and one person is in the oppositional reading category.